Cytotoxicity and Genotoxicity of Biogenic Silver Nanoparticles in A549 and BEAS-2B Cell Lines - Musthahimah Muhamad; Nurhidayah Ab.Rahim; Wan Adnan Wan Omar; Nik Nur Syazni Nik Mohamed Kamal (Bioinorganic Chemistry and Applications)
Introduction. Biogenic silver nanoparticles (AgNPs-GA) were successfully synthesised using Garcinia atroviridis leaf extract as a reducing agent, which has ethnopharmacological claims against various diseases including cancer. Aim of the Study. Aim of the study is to discover whether AgNPs-GA has cytotoxic and genotoxic effects on cancerous (A549) and noncancerous (BEAS-2B) human lung cells. Materials and Methods. The cytotoxicity profiles of AgNPs-GA were characterized by MTT assay, intracellular reactive oxygen species (ROS) assay, and DAPI and AOPI double staining, whilst genotoxicity was assessed using Comet Assay analysis. The level of silver ions (Ag+) and cellular uptake of AgNPs-GA were evaluated by ICP-OES and TEM analyses, respectively. Results. A significant cytotoxic effect was observed by AgNPs-GA on both A549 and BEAS-2B cell lines, with IC50 values of 20–28 μg/ml and 12–35 μg/ml, respectively. The cytotoxicity profile of AgNPs-GA was also accompanied by a pronounced increase in ROS production, DNA damage, and apoptosis. Moreover, Ag+ was also detected in cells exposed to AgNPs-GA threefold higher compared to controls. In this study, AgNPs-GA were endocytosed within lysosomes, which may direct to secondary toxicity effects including oxidative stress, impairment of the cell membrane, DNA fragmentation, and cell death. Conclusions. Taken together, novel toxicological-related mechanisms by AgNPs-GA were proposed involving the generation of ROS that causes DNA damage which led to programmed cell death in both A549 and BEAS-2B cells. Therefore, a combination of scientific assessments is constantly needed to ensure that the quality of biosynthesized nanoparticles is controlled and their safe development is promoted.